Colombia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
This paper quantifies the dynamic effects of fiscal policy using a structural model, the Global Integrated Monetary and Fiscal Model (GIMF). The analysis finds that success of fiscal policy in enhancing macroeconomic stability depends on the type of shock, the response of monetary policy, and the length of fiscal policy implementation lags. The paper also presents the basic structure of the Bayesian VAR describing its empirical implementation and the estimation results and results from the conditional forecasting exercise and remarks. It also assesses Colombia's experience with central bank foreign exchange intervention between 2004 and 2007.